Muslim Societies, Civil and Political Rights, and The Guarantee of Religious Freedom: A Comparative Study Between Indonesia and Turkiye Constitutions - Ahyar, Muzayyin; Materan, Materan; Muqorrobien, Muhammad Kholil (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Until the middle of the 20th century, many Muslim population countries became free and independent countries following the end of world colonization. Those countries try to adopt several modern political and legal values, including establishing democracy and state constitutions. One of the constitution's contents in a democratic country is guaranteeing and strengthening civil and political rights. Civil and political rights regulation should be written in a partial part of the constitution as a commitment to live in modern democratic circumstances. Philosophically, citizens' civil and political rights in democratic circumstances cannot be restricted by government. Nevertheless, a gap in the legal argument regarding the limitation of civil and political rights in constitutions is constantly discussed. This article looks at civil and political rights limitations in two cases in different countries: Indonesia and Turkiye. These two countries were chosen as subjective data based on the legal system's proximity pattern and socio-religious conditions. Both countries are also close to the civil law system and have historical references to Islam. In addition, both countries have experience with the restriction of religious organizations. Indonesia has dealt with the restriction of Hizbut Tahrir Movement. Meanwhile Turkiye has experience in banning Gulen Movement. By this background, some questions emerge: How do Indonesian and Turkish constitutions, as Muslim population countries, guarantee human rights issues? By using a comparative legal study and a sociological-empirical approach, this article compares the Indonesian and Turkiye constitutions to see how the two countries guarantee human rights, predominantly civil and political rights. The result of this article reveals that national consensus, national security, stability, and legitimate political power are some of the legal arguments that are always present in the discourse on restrictions on human rights. Under these conditions, human rights restrictions are commonly regulated in the constitution, which contains human rights laws.